The Implementation of Flipped Classroom by Using LMS (Learning Management System) at SMA NEGERI 6 Tanjungpinang in the Academic Year 2020/2021 - Duwi Novita Sari; Dewi Nopita; Gatot Subroto (Juliet, 2022)
This study aimed to describe how the implementation of flipped classroom by using LMS (Learning Management System) at SMA NEGERI 6 Tanjungpinang. The research design in this study was descriptive qualitative research. The participants of this study were the English teacher and students of XI MIPA class in the English subject at SMA NEGERI 6 Tanjungpinang in the academic year of 2020/2021. The instruments for collecting the data were questionnaires and interviews. The questionnaires in this study was developed by Song (2010) there were 5 indicators, namely students’ interest, ease of access, perceived usefulness, perceived instruction delivery, and students’ satisfaction. Then, the interviews in this study was developed by Almrashdeh (2011) there were 3 indicators, namely planning of specific learning process, implementation of specific learning process, and assessment of specific learning process. The results of data analysis revealed that the implementation of flipped classrooms by using LMS (Learning Management System) at SMA NEGERI 6 Tanjungpinang was quite good.